Multicultural Education and Its Impact on the Character of Religious Moderation in Students at Pancasila Islamic Boarding School, Bengkulu City - Dilly Yuwita Utami; Enggar Aditya Widiyanto; Jasrin Abito; Asniti Karni; Dayun Riadi (Yayasan Sembilan Pemuda Indonesia, 2026)
This study analyzes the implementation of multicultural education in shaping students’ character at the Pancasila Islamic Boarding School in Bengkulu City. The research focuses on three primary aspects: the forms of multicultural education, the strategies employed by kyai and ustadz in instilling multicultural values, and the subsequent impact on students’ character. Using a qualitative case study approach, data were collected through observation, in-depth interviews, and documentation. The analysis followed the interactive model of Miles, et. al., (2020) with triangulation techniques ensuring data validity. The findings reveal that multicultural education is implemented comprehensively by integrating the Islamic values of rahmatan lil ‘alamin with spirit of nationalism into the curriculum, social activities, and institutional culture. Key strategies include exemplary leadership (uswah hasanah), communal living, intercultural dialogue, and strengthening of national values. The result indicates a significant enhancement in students’ religiosity, tolerance, and national awareness. This study’s novelty lies in its contextual analysis of boarding school that harmonizes Islamic principles with Pancasila as the foundation of multicultural education. Practically, it demonstrates that Islamic boarding schools can serve as inclusive educational models for fostering a moderate and patriotic Muslim generation.